Does the new protectionsm really harm all trading countries? - Franz Peter Lang (Intereconomics, 1989)
The following article considers the effects triggered by exporting countries' reactions to the new protectionism. It demonstrates that if the analysis is broadened to take account of macro-economic interdependence the assessment of the trade interests, for instance, of “new” exporting countries such as the NICs must be revised
Keywords: 330; Protectionism